The role of CRF type-1 receptors in the VTA and DRN in excessive alcohol drinking in rats and mice. - Hwa, Lara. (2017)
Abstract: The dysregulation of brain stress systems, specifically extrahypothalamic action of corticotropin-releasing factor (CRF) via the type-1 receptor (CRF-R1), is thought to mediate escalated, alcohol drinking. The current study modeled excessive drinking in rodents by offering adult male Long-Evans rats and C57BL/6J mice a choice of 20% ethanol or water for 24 hours intermittently throughout the week. After escalated baseline drinking was established, animals received several doses of a CRF-R1 antagonist into either the ventral tegmental area (VTA) or the dorsal raphé nucleus (DRN) aiming to decrease alcohol drinking. CP-154,526 selectively reduced ethanol drinking in the VTA in all animals whereas only the high alcohol preferring animals, the mice and high-preferring rats, showed this decrease in the DRN. Since CP-154,526 reduced water intake in the DRN, we demonstrated a differentiation between brain sites in how selective CRF-R1 antagonism can act to suppress elevated ethanol drinking in some individuals but not others.; Thesis (M.S.)--Tufts University, 2011.; Submitted to the Dept. of Psychology.; Advisor: Klaus Miczek.; Committee: Joseph DeBold, and Michael Romero.; Keywords: Physiological psychology, and Behavioral sciences.